Research of transformation changes in the noncommercial organizations’ management process in the conditions of military aggression - Olena Kanishchenko; Nataliia Chupryna; Hanna Dotsenko; Vira Zhuravel; Mariia Khudomaka (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The organizational and logistical transformation of the educational process is one of the components of the effective functioning of educational institutions that cannot work on their territory as a result of the military actions of the Russian Federation. The stages of the transformation of the educational process in wartime conditions must be investigated and their relevance determined in one or another situation. Their number is determined under the influence of many factors, but the main one is ensuring personal safety and preserving the health of people and animals involved in the transformation process. Solving the problems of organizational and logistical transformation is impossible without a detailed understanding of the essence of the educational process in the conditions of military operations. The educational process can be provided by various forms of information provision. Already during the period of the COVID-19 pandemic, all subjects of the educational process (both those who provide content and those who consume it) learned to work online and independently perform tasks, sending them to the teacher on Internet platforms that ensured quality and efficiency distance learning. The Law of Ukraine “On Education” provides a clear definition of the educational process category. The educational process is a system of scientific, methodical and pedagogical activities aimed at the development of the individual through the formation and application of his competencies [1]. However, it should be noted that in order for this system of scientific-methodical and pedagogical measures to be carried out in full and of proper quality, it is necessary to ensure a number of conditions. The most important of these conditions is the safety of people participating in the educational process. Changes in the educational process began to take place, even during the period of COVID-19, but they were due to the global pandemic, and not to military actions, as in the present time. The peculiarity of the change in the educational process in the conditions of military operations is the logistical transformation of educational institutions, both universities and vocational and technical schools.